La expresión plástica infantil y su relación con el desarrollo de la pre escritura de las niñas y niños del primer año de educación básica de la unidad educativa Lauro Damerval Ayora nº1, periodo 2012-2013 - Regalado Rodriguez, Lidice Gladis; Rentería Rentería, Ruth Patricia (2015)
This research work was aimed to investigate: PLASTIC EXPRESSION AND ITS RELATIONSHIP WITH BASIC GENERAL EDUCATION FIRST YEAR CHILDREN PREWRITING DEVELOPMENT “LAURO DAMERVAL AYORA N º 1", PERIOD 2012-2013, whose overall objective was to analyze the relationship between the Children's Artistic Expression and Basic General Education First Year Children Prewriting Development "Lauro Damerval Ayora Nº1" School, period 2012-2013. Scientific, empirical, deductive, inductive, bibliographic; and model statistical for the development of this research work methods were used. In conducting the research technique used was: the survey was directed to the teacher and observation guide was applied to children the field research was developed with a total of 64 students and five teachers. It was evident that techniques of plastic expression and graph-plastics that used more frequently in their journeys of classes teachers are 100% the bucking, the Dactyl painting, tearing, cut with scissors, crumpled paper, painted, modeling, scribbling, punching, the technique of kneading, folding in 60% and stew in 20%, 100% the technique of drawing and painting technique, and 60% technique of crayons more than it made plastic activities every day in 80% and according to the planning 20%, these techniques are important because they allow the development of pre-writing. The objective test applied to children results demonstrate that the required learning (SAR) exceed a percentage of 55% to 76% of children, 30% to 34% dominate the required learning (DAR) and a percentage of 8% to 11% reach the required learning (AAR), allowing you to verify that children have a good graph-motor development that significantly affects the pre-writing process.